Only rheumatoid factor‐positive subset of anti‐citrullinated peptide/protein antibody‐negative rheumatoid arthritis may seroconvert to anti‐citrullinated peptide/protein antibody‐positive. (15th February 2017) - Hiwa, Ryosuke; Ohmura, Koichiro; Nakabo, Shuichiro; Terao, Chikashi; Murakami, Kosaku; Nakashima, Ran; Imura, Yoshitaka; Yukawa, Naoichiro; Yoshifuji, Hajime; Hashimoto, Motomu; Furu, Moritoshi; Ito, Hiromu; et al.
Abstract: Aim: Anti‐citrullinated peptide/protein antibody (ACPA) has been reported to occur in about 60% of patients with early rheumatoid arthritis (RA), and about 80% in patients with established RA. While ACPA seroconversion is possible, previous reports have shown that it rarely occurs. We retrospectively determined the proportion of patients who underwent ACPA seroconversion and described the clinical characteristics of these cases. Methods: ACPA‐negative RA patients who had undergone ACPA assessment more than once with an interval of 3 months or longer were investigated for ACPA seroconversion. The clinical characteristics of seroconverted patients were assessed. Results: In 149 ACPA‐negative RA patients, only eight patients (5.4%) converted to ACPA‐positive during follow‐up. We found that all eight of the seroconverted cases were positive for rheumatoid factor (RF) and showed bone erosions by X‐ray. Of 56 ACPA‐negative RF‐positive RA patients, 14.3% of them seroconverted to ACPA‐positive. None of the ACPA‐negative RF‐negative RA patients seroconverted to ACPA‐positive. Conclusion: The proportion of total RA patients who experienced seroconversion from ACPA‐negative to ACPA‐positive was 5.4%. When ACPA‐negative RA patients were subdivided into RF‐negative and RF‐positive subsets, only the RF‐positive subset seroconverted to ACPA‐positive. These results imply that RF‐negative and RF‐positive patients are distinct subsets within ACPA‐negative RA patients.